The efficacy of rhomboid intercostal block for pain management after video-assisted thoracoscopic surgery: a prospective, randomized-controlled trial - Çiftçi, Bahadır; Alver, Selçuk; Güngör, Hande; Gölboyu, Birzat Emre; Subaşı, Mahmut; Ömür, Burak; Gül, Yaşar Gökhan; Ekinci, Mürsel (My University, 2024)
Objective: We aimed to evaluate the efficacy of rhomboid intercostal block (RIB) for analgesia management in patients who underwent video-assisted thoracoscopic surgery. Methods: Adult patients who underwent VATS under general anesthesia between July 2020 and June 2022 were included in the study. There was two groups in this study: RIB (n = 25) vs control (n = 25) group. RIB was performed with 30 ml 0.25% bupivacaine at the end of the surgery. Surgical intercostal blockade was performed with 30 ml 0.25% bupivacaine in the control group. The patients received intravenous fentanyl patient-controlled postoperative analgesia. The numerical rating score (NRS), opioid consumption, and adverse events were recorded. Results: A total of 50 patients were randomized into 2 groups. There were no significant difference in terms of the demographic data between groups (P > 0.05). Postoperative opioid consumption at 0–8, 8–16, 16–24, and 24–48 h and rescue analgesic use were significantly lower in RIB group (P < 0.05). At all times, the static/dynamic NRS were significantly lower in RIB group. The rate of nausea and itching was higher in control group (P < 0.05). Conclusion: US-guided RIB provides effective post-VATS analgesia.
Keywords: Intercostal Block; Postoperative Analgesia; Rhomboid Intercostal Block; Video-Assisted Thoracic Surgery